ANALISIS MANAJEMEN ARUS KAS UNTUK MENGUKUR LIKUIDITAS PT. KARYA DAYUN KABUPATEN SIAK - Abdilah, Rizki Utmah; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to determine and analyze cash flow management to measure the liquidity of PT. Karya Dayun Siak Regency from 2015 to 2019 using cash flow ratios and liquidity ratios. The type of research used in the form of secondary data which is data from financial statements. The data collection technique used is the method of documentation and interviews. The data analysis technique used is to calculate the cash flow ratio, namely Operating Cash Flow Ratio (AKO), Cash Coverage Ratio to Current Debt (CKHL), Total Debt Ratio (TH), Capital Expenditure Ratio (PM) and liquidity ratio, namely Current Ratio (Current Ratio). Ratio) and Cash Ratio (Cash Ratio).                Based on the results of the financial data analysis of PT. Karya Dayun Siak Regency that liquidity in 2015-2019 in terms of cash flow management got poor results, only in calculating the CKHL ratio the company's liquidity was in very good condition. The company's ability to pay its short-term obligations in terms of the current ratio is in very poor condition and the company's ability to provide cash to pay its short-term obligations is in poor condition.  Keywords: Statement of Cash Flows, Liquidity